PENGEMBANGAN BAHAN AJAR BERBASIS DIGITAL STORYTELLING DENGAN TEKNOLOGI AI GENERATIF MELALUI PLATFORM BOOK CREATOR DI SMPN 1 BOJONG, PANDEGLANG - Irma Savitri Sadikin; Abdul Halim; Hardianti Hardianti; Lutfiyah Lutfiyah; Imam Sutanto (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
This community service program aimed to enhance the competencies of teachers at SMPN 1 Bojong, Pandeglang, in developing digital learning materials based on digital storytelling integrated with Artificial Intelligence (AI) technology. The program was initiated in response to the limited utilization of interactive digital learning media among teachers, particularly in semi-rural areas, despite the availability of basic infrastructure such as digital devices and internet connectivity. Preliminary observations revealed that approximately 80% of teachers still relied on lecture-based methods and static presentations, resulting in learning activities that were less contextual and less engaging for students, who tend to exhibit visual learning preferences. To address this issue, the program implemented practice-oriented training combined with continuous mentoring in the use of several digital platforms, including Book Creator, ChatGPT/Gemini, Bing Image Creator, and ElevenLabs. The implementation process consisted of several stages, namely program socialization, intensive training workshops, digital material development, mentoring for implementation, and program evaluation. The results indicated that 19 out of 21 participating teachers (90%) successfully developed prototype digital learning materials based on storytelling integrated with AI tools. In addition, the program produced 13 digital teaching materials stored in a school-based cloud repository, an instructional e-booklet on developing AI-supported digital learning materials, and the establishment of a community of practice among teachers focused on digital innovation. Evaluation results further revealed that 86% of participants reported improved competencies in utilizing AI technologies for instructional media development.